Follicular Response by using Letrozole alone or combination of Letrozole and Gonadotrophins in patients stimulated for IUI - Rahman, F; Mahmud, N; Chowdhury, TA; Rahman, RRB; Begum, B (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
IUI with controlled ovarian hyperstimulation is a well known means to achieve pregnancy in unexplained and mild to moderate male factor infertility, which is also inexpensive, easy to perform as office procedure. The success rate is high. Objective: To assess the follicular response by Letrozole alone or by combination of Letrozole and Gonadotrophins in patients stimulated for IUI. Method: Prospective observational type of study. Place: CARE BIRDEM Time: 10th May 2010 31st December 2010 Population: All the OPD patients of CARE who were selected for IUI during this period. Patients were divided into two age groups (<30 yrs and >30 yrs) Procedure: Ovulation induction was done by letrozole in one group, and combined letrozole and gonadotrophins in another group. Monitoring was done by TVS for 3 cycles. Result: Mean follicular number was 1.28±0.94 in letrozole and 3.37±0.87 in combined letrozole and gonadotrophins. No. of follicles >18mm was 12 pts (3.54±1.63) in letrozole, and 50 pts (3.44±1.93) in combined letrozole and gonadotrophins. Pregnancy/cycle was 12/77 (5.19%) in letrozole and 28/65 (14.3%) in combined letrozole and gonadotrophins. Conclusion: Number of mature follicle and pregnancy rate is higher in combined letrozole and gonadotrophins group than letrozole alone. There is no significant difference regarding follicular response and pregnancy rate in two age group DOI: http://dx.doi.org/10.3329/bjog.v26i1.13755 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 20-26